Viralisasi Bermakna: Etika dan Efektivitas Strategi FYP dalam Merekonstruksi Konsumen Gen-Z - Izzatul Mula; Auliya Ristiani; Ningrum Puji Lestari (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
TikTok's algorithm-based digital marketing strategy, especially through the #FYPMarketing approach, has become an effective method in building emotional connections and increasing Gen-Z consumer loyalty. Through the For You Page (FYP) feature, brands can spread content organically with a wide reach, as long as the content is emotionally relevant, authentic, and participatory. This study uses a qualitative method based on literature studies and analyzes the #ScarlettGlowUp campaign as a case study. The findings show that the success of marketing to Gen-Z is greatly influenced by the use of user-generated content, micro-influencer involvement, and storytelling that is consistent with the values ​​held by the audience. However, challenges such as algorithm manipulation, digital communication ethics, and data privacy issues are obstacles that require an approach based on transparency and social responsibility. This article concludes that the success of the #FYPMarketing strategy depends not only on technological and algorithmic capabilities, but also on trust, clarity of values, and alignment between the brand and its digital community.